Novel usage of the curved rectangular fin on the heat transfer of a double-pipe heat exchanger with a nanofluid - Jalili, Bahram; Aghaee, Narges; Jalili, Payam; Domiri Ganji, Davood (Case studies in thermal engineering, 2022)
The convection heat transfer in a countercurrent double-tube heat exchanger with various fins in a turbulent flow is investigated. The suitable heating or cooling process of fluids is the effective use of the double-pipe heat exchanger. We use water-aluminum oxide nanofluid and water-titanium dioxide at four concentrations (0.4%, 2%, 4%, 6%) as the cold fluid in the inner tube and water as the hot fluid in the annular space. The single-phase model for nanofluid modeling and the standard k-ε model with scalable wall function for simulating the turbulent flow is utilized. To better examine this novel geometry, its performance is compared with simple and rectangular-finned geometries. The results show that the water aluminum oxide nanofluid has a better convection heat transfer coefficient than water titanium dioxide and pure water. Raising the nanofluid concentration from 0.4% to 6% increases the convection heat transfer coefficient by 12%. Heat exchangers with a rectangular and curved fin have 81% and 85% better efficiency than the heat exchanger without a fin. The novel geometry causes a smaller pressure drop despite its higher convection heat transfer coefficient. Also, it is shown that with raising the Reynolds number and nanofluid concentration, the pressure drop increases.